Clinical and otorhinolaryngological aspects of extranodal NK/T cell lymphoma, nasal type - Miyake,Marcel Menon (2014)
INTRODUCTION: Extranodal NK/T-Cell lymphoma, nasal type (NKTLN) is a disease that mainly affects the nasal cavity and the paranasal sinuses. Early nasal symptoms are nonspecific, simulating sinus infection. With disease progression, necrosis of the nasal mucosa increases, hindering histological diagnosis. Thus, multiple biopsies may be necessary until definitive diagnosis. Most studies on NKTLN address the hematological and immunological aspects of the disease. OBJECTIVES: To present data from a Brazilian quaternary hospital, with emphasis on the clinical aspects of the disease, and to correlate the findings with the most recent literature data. METHODS: Case study of seven patient files. RESULTS: Patients were evaluated on their medical history, number of biopsies necessary, association with Epstein-Barr virus, treatment, and outcome. All patients had nonspecific nasal complaints and underwent at least three cycles of antibiotic therapy. The earlier a biopsy was performed, the fewer biopsies were required to diagnose the disease and start treatment. However, this fact did not translate into better prognosis. CONCLUSION: The otolaryngologist plays a fundamental role in the prognosis of NKTLN and can shorten time between symptom onset and treatment of the patient.